2010
DOI: 10.1177/0306624x10378231
|View full text |Cite
|
Sign up to set email alerts
|

Correctional Officers’ Perceptions of a Solution-Focused Training Program

Abstract: The purpose of this exploratory study was to explore correctional officers' perceptions and experiences during a solution-focused training program and to initiate development of a modified pattern for correctional officers to use in jails. The study uses grounded theory procedures combined with a follow-up survey. The findings identified six emergent themes: obstacles to doing counseling work in prisons, offenders' amenability to change, correctional officers' self-image, advantages of a solution-focused appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 19 publications
2
15
0
1
Order By: Relevance
“…Had the study investigated the work stresses of correctional officers, such as dangerous situations, threats to personal safety, long hours of work, low salaries, little social support, scarce opportunities for career enrichment, high turnover rates, burnout, dissatisfaction with work, high rates of absenteeism, or illness (Pan et al, 2011;Parker, 2009), the study may have found a strong relationship between these variables and correctional officers' self-efficacy beliefs.…”
Section: Chapter 5 Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Had the study investigated the work stresses of correctional officers, such as dangerous situations, threats to personal safety, long hours of work, low salaries, little social support, scarce opportunities for career enrichment, high turnover rates, burnout, dissatisfaction with work, high rates of absenteeism, or illness (Pan et al, 2011;Parker, 2009), the study may have found a strong relationship between these variables and correctional officers' self-efficacy beliefs.…”
Section: Chapter 5 Discussionmentioning
confidence: 99%
“…Correctional officers work in a stressful environment. Pan, Deng, Chang, and Jiang (2011) reported that correctional staff generally experience needs for training, pay increase, career enrichment opportunities, and a more positive public image. Among the many stressors of correctional work, Pan et al identified "role problems, work overload, demands for social contact (with prisoners, colleagues, and supervisors), and poor social status" (p. 865) as most notable.…”
Section: Mental Illness In Correctional Settingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Для того чтобы осуществлять свою власть надлежащим образом, представители власти должны верить в свою легитимность. Самооценка представителей власти есть сочетание черт, ценностей, мыслей и чувств и в значительной степени формируется из восприятия того, что думают о них другие, и это соответствующим образом влияет на их действия [45].…”
Section: юридические наукиunclassified
“…The solution-focused approach program (SFAP; Guterman & Leite, 2006) had been further developed by Pan et al (2011). The content of the SFAP covered three areas: the basic assumptions of SFA, advanced SFA theory, and particular SFA techniques and applications for military instructors to deal with student clients' personal concerns.…”
Section: Program Descriptionmentioning
confidence: 99%